Changes in Livelihood Practices, Strategies and Dependence on Bushmeat in Two Provinces in Gabon. (1st March 2019) - Van Gilsa, E.J.T.; Ingrama, V.J.; Ipongab, D. Midoko; Abernethyb, K.
Traditional, forest resource-dependent livelihoods face multiple challenges. In Gabon, bushmeat provides food and income for rural communities. This study investigates how villagers believe livelihood practices and dependence on bushmeat changed over the last decade and if alternative income and food generating strategies can be sustainable. Our results show that remote villages near Moukalaba Doudou National Park hardly changed practices. Less remote villages near Tchibanga experienced declining hunting revenues and are switching to alternatives. Villages near Libreville almost completely changed strategies, and are no longer dependent on forest resources. Changes in livelihood practices were driven either by resource depletion or urbanization. The ability to change depended on proximity to facilities and infrastructure. Although most respondents were able to change, not all alternative strategies are sustainable. The results highlight the need to evaluate the long-term effectiveness of alternative poverty reduction and nature conservation strategies in a context of urbanization and food security. There is a need to reduce bushmeat demand, making supply more sustainable through effective resource governance and creating a conducive institutional and policy environment.